Distinctive Feature of Phoneme in Savunese Language - Rudolof Jibrael Isu (International Conference on Education and Language (ICEL), 2014)
Savunese language later shortened (Sl) is a regional language used by East Nusa Tenggara people particularly Sabu and Raijua. The area of using Savunese language can be found in Ipi/Ende regency, Aimere/Ngada regency, Melolo/East Sumba regency, Kupang city, Kupang regency, Soe regency, Kefa regency andBelu regency; the functionof Savunese languageas introductory language for Savunese people in the overseas still functions properlybecause of traditional lifestyle of the group based on the origin and interest which is still very dominant. In this paper I attempt to appoint the mistery of the distinctivefeature of phoneme in Savunese language, is a concern to bring back the uniqueness of Savunese language which has undergone a lot of developments. The determination of consonant features according Optimization Theory based on the following criteria: (1) classification based on place of articulation , (2) classification based on the sound , (3) classification based on nasality , and (4) classification based on continuity (continuation). While the determination of vowel in Savunese language. Structural or transformational-generative idiologyuses high, mid, low, front, back, round, and non roundin classifying vowel. Unlike the Structural ideology, Generative ideology describes vowel by using distinctive features [high], [back.], [round.], and [low].